Preparation and Characterization of (MCM-41)-Carvedilol Composite Material - Hu, Wei-Hua; Zhai, Qing-Zhou; Xv, Yun-Peng (Asian Journal of Chemistry, 2012)
With sharply increase in the amount of patients with elevated blood pressure population, seeking the effective treat medicine and the loading medicine carrier becomes a hot research spot. This paper used MCM-41 to take a carvedilol medicine carrier using hydrothermal method to synthesize MCM-41 and in it carvedilol was loaded. The amount of assembly capacity was 180 mg/g (drug/MCM-41). The prepared composites were characterized by chemical analysis, powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy and N2 adsorption-desorption and the release law in human body simulated fluid was made. Powder X-ray diffraction showed that during the process of incorporation the framework of the molecular sieve was not destructed and crystalline degrees of molecular sieve in the host-guest composite materials prepared were still very high. FT-IR spectra showed that the frameworks of host molecular sieves of the prepared host-guest composite materials were intact. Low-temperature nitrogen adsorption-desorption results at 77 K showed that the specific surface area and the pore volume of the host-guest composite material decreased compared to those of the host molecular sieve, indicating that the guest has partially occupied the channels of the molecular sieve. Transmission electron microscopic results showed that two-dimensional hexagonal mesoporous channels of molecular sieve in the composite materials were maintained. Scanning electron microscopic results showed that the composite materials were maintained as fibrous crystals. In simulated body fluid, it is discovered by studying release law of drug in the composite materials that drug release effective time was up to 32 h and release ratio was 99.4 %. In simulated gastric fluid, composite drug release time was up to 4 h and release rate was up to 23 %. In simulated intestinal fluid, the drug release time up to 9 h can be more effective and the release rate was 72.7 %. The above results showed that MCM-41 is a well-controlled drug delivery carrier.